PROJECTIVE METHODS IN PERSONAL STUDY ANALYSIS OF ADVANTAGES (Scientific journal of the Fergana State University, 2023)
This article describes the diagnostic possibilities, advantages and disadvantages of projective methods in the study of personality. The procedures for conducting one of the projective methods are also analyzed, which help to determine the characteristics and interests of a person. Important features of projective methods in human research are that these methods are aimed at measuring the characteristics and intelligence of a person, depending on the task assigned to the respondent, that is, those who are asked, and the nature of catching and interpreting the results. In a word, projective methods are a type of testing method in which the test-taker is presented with ambiguous items that are not clearly visible to the test-taker and is asked to interpret them. This method helps to identify and evaluate the hidden, unrealized sides of a person.